2000
DOI: 10.1091/mbc.11.5.1657
|View full text |Cite
|
Sign up to set email alerts
|

Endoplasmic Reticulum Quality Control of Oligomeric Membrane Proteins: Topogenic Determinants Involved in the Degradation of the Unassembled Na,K-ATPase α Subunit and in Its Stabilization by β Subunit Assembly

Abstract: The molecular nature of determinants that mediate degradation of unassembled, polytopic subunits of oligomeric membrane proteins and their stabilization after partner subunit assembly is largely unknown. Expressing truncated Na,K-ATPase ␣ subunits alone or together with ␤ subunits, we find that in unassembled ␣ subunits neither the four N-terminal transmembrane segments acting as efficient alternating signal anchor-stop transfer sequences nor the large, central cytoplasmic loop exposes any degradation signal, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
58
1
2

Year Published

2000
2000
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(64 citation statements)
references
References 42 publications
3
58
1
2
Order By: Relevance
“…The ␤-subunit of Na ϩ /K ϩ -ATPase serves as a chaperone that promotes proper membrane insertion of the ␣-subunit. After formation of the holoenzyme, the ␤-subunit stabilizes the ␣-subunit in the membrane and modulates cation sensitivity of the pump (48,49). In this study, we confirmed that NDRG2 directly interacted with Na ϩ /K ϩ -ATPase ␤1 using co-immunoprecipitation.…”
Section: Discussionsupporting
confidence: 70%
“…The ␤-subunit of Na ϩ /K ϩ -ATPase serves as a chaperone that promotes proper membrane insertion of the ␣-subunit. After formation of the holoenzyme, the ␤-subunit stabilizes the ␣-subunit in the membrane and modulates cation sensitivity of the pump (48,49). In this study, we confirmed that NDRG2 directly interacted with Na ϩ /K ϩ -ATPase ␤1 using co-immunoprecipitation.…”
Section: Discussionsupporting
confidence: 70%
“…The Na/K-ATPase ␤ subunit has been generally prescribed to serve two primary roles including 1) a chaperone role that directs the insertion of the ␣ subunit and functional enzyme unit to the appropriate membrane domain (22)(23)(24)(25) and 2) the regulation of cation sensitivity of the Na/K-ATPase (26 -28). Most recently, however, an additional role in regulating epithelial cell phenotype and cell motility has been defined for the Na/K-ATPase ␤ subunit (29 -35).…”
Section: Discussionmentioning
confidence: 99%
“…Only the ␣ 1 subunits that assemble with the ␤ 1 subunits exit the ER and reach the plasma membrane. It has been shown in various expression systems that the ␣ 1 subunit alone is not able to exit the ER and is degraded (27). If the expressed H,K-ATPase ␤ subunit assembles with the endogenous Na,K-ATPase ␣ 1 subunit in MDCK cells, the amount of the Na,K-ATPase ␣ 1 subunit present in the plasma membrane must be greater in the cells expressing the H,KATPase ␤ subunit compared with nontransfected cells.…”
Section: Fig 1 Steady State Distribution Of the Wild Type (Wt) Or Mmentioning
confidence: 99%